Comparisons between off-axis detection and on-axis recognition to implement mesopic photometry in roadway lighting standards. (June 2020) - Ohashi, R; Akashi, Y; Uchida, T
Mesopic photometry can be applied to road lighting practice to enhance peripheral visual performance and to reduce light levels. However, mesopic photometry characterizes peripheral vision, whereas photopic photometry characterizes foveal vision at all light levels. Higher scotopic / photopic ( S / P ) ratio light sources which enhance peripheral visual performance may have a negative influence on foveal vision. In addition, light level reductions, as realized in British Standard 5489-1: 2013, may impair foveal visual performance. To investigate the above-described concern, we conducted two experiments. First, we investigated whether Landolt ring targets detected by peripheral vision can be recognized correctly after moving the line of sight to fixate on the targets in foveal vision. Then, we found that subjects could recognize in foveal vision almost all targets that peripheral vision detected. The S / P ratio of the background lighting did not influence this tendency. Second, we investigated luminance contrast thresholds for foveal vision to compare them with those for peripheral vision, obtained from the first experiment. We found that threshold contrasts of targets recognized by foveal vision were lower than those detected by peripheral vision. These results lead to the conclusion that the use of higher S / P ratio light sources has no negative influence for foveal vision when implementing mesopic photometry.